2006
DOI: 10.1007/s11095-006-9059-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Oral Efficacy of Recombinant Granulocyte Colony-Stimulating Factor and Transferrin Fusion Protein by Spacer Optimization

Abstract: The insertion of a linker peptide, such as the helix linker H4-2, between G-CSF and Tf domains in the recombinant fusion protein can improve significantly both in vitro and in vivo myelopoietic activity over the non-linker fusion protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
80
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 32 publications
4
80
0
Order By: Relevance
“…PEGylation, [7] acylation, [8] or glycosylation [9] ), fusion with or binding to plasma proteins (e.g. albumin, [10] transferrin, [11] or Fc fragments [12] ) has yielded numerous clinical protein candidates with improved PK/PD profiles. The binding of a polypeptide drug (either covalently or through a tightly binding carrier) to long-lived plasma proteins in the bloodstream enables tight control over targeted drug levels with improved exposure and distribution in the circulation that may potentially lead to lower doses, decreased side effects, and enhanced predictability.…”
mentioning
confidence: 99%
“…PEGylation, [7] acylation, [8] or glycosylation [9] ), fusion with or binding to plasma proteins (e.g. albumin, [10] transferrin, [11] or Fc fragments [12] ) has yielded numerous clinical protein candidates with improved PK/PD profiles. The binding of a polypeptide drug (either covalently or through a tightly binding carrier) to long-lived plasma proteins in the bloodstream enables tight control over targeted drug levels with improved exposure and distribution in the circulation that may potentially lead to lower doses, decreased side effects, and enhanced predictability.…”
mentioning
confidence: 99%
“…Such surprising results confused us after at least five times determination. Bai & Shen (2006) indicated that the loss of activity of one moiety is not due to a simple steric hindrance, but rather due to the alteration of the intrinsic conformation of domain in the fusion protein, and such conclusions may offered an explanation for our experimental results.…”
Section: Discussionmentioning
confidence: 56%
“…The linker displayed α-helical conformation, which was stabilized by the Glu − -Lys+ salt bridges within segments. They had already been applied to the construction of many recombinant fusion proteins [Amet et al, 2009;Bai and Shen, 2006].…”
Section: Discussionmentioning
confidence: 99%